EFEK KO-KEMOTERAPI FRAKSI ETIL ASETAT AKAR PASAK BUMI DAN DOXORUBICIN TERHADAP PROLIFERASI DAN EKPRESI BAX JARINGAN PAYUDARA TIKUS SD - Tria Zakinah; Laela Hayu Nurani; Sitarina Widyarini (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2017)
The use of co-chemotherapy agent was needed since there were some toxicities on the normal tissues caused by the use of doxorubicin. The root of Eurycoma longifolia Jack, a part of plant, has a potential activity as co-chemotherapy. This study aimed to determine the effect of co-chemotherapy of ethyl acetate fraction of E. longifolia Jack roots and doxorubicin against cell proliferation activity by AgNOR method and determine expression of Bax protein of breast tissue in rats induced by DMBA. The rats were divided into five groups: I (baseline), II (DMBA 20 mg/kgBW), III (DMBA, doxorubicin 1.12 mg/kg), IV (DMBA, fraction of 100 mg/kg), and V (DMBA, doxorubicin, fractions). All the rats were sacrificed at week 16. Their breast tissue was evacuated. Cell proliferation and expression was observed using AgNOR method and immunohistochemistry, respectively. Results showed the percentage of p-AgNOR obtained by the healthy group, DMBA group, DMBA+Doxorubicin group, DMBA+ethyl acetate fraction of E. longifolia Jack root group, and DMBA+Doxorubicin+Ethyl acetate fraction of E. longifolia group were 00%, 14.672.11%, 1.831.21%, 6.832.03%, and 4.080.95%, respectively. The percentage of Bax expression obtained by the healthy group, DMBA group, DMBA+Doxorubicin group, DMBA+ethyl acetate fraction of E. longifolia Jack root group, and DMBA+Doxorubicin+Ethyl acetate fraction of E. longifolia group were 68.821.52%, 26.863.25%, 44.492.06%, 80.923.27%, and 78.704.87%, respectively. Based on the results, it was concluded that co-chemotherapy agent of ethyl acetate fraction of E. longifolia Jack roots and Doxorubicin could inhibit proliferation and trigger apoptosis through Bax expression in breast tissue of rats induced by DMBA.